Implementasi Kebijakan Kurikulum Merdeka Di Sd Negeri Kloposepuluh 2 Kec. Sukodono Kab.Sidoarjo - Fatimah, Siti; Haryati, Eny (Soetomo Magister Ilmu Administrasi, 2023)
This study aims to identify and analyze the implementation of the Independent Curriculum policy at Kloposepuluh State Elementry School 2 Sukodono - Sidoarjo Regency and its supporting and inhibiting factors. This research includes the type of qualitative descriptive research. The theory used in this study is the theory of policy implementation according to George Edward III, with 4 variables namely communication, resources, disposition and bureaucratic structure. The collection of research data was carried out through observation, interviews, document studies. Furthermore, the data analysis used is data condensation, data presentation and drawing conclusions.The results of the study found that the implementation of the Freedom Curriculum policy at Kloposepuluh State Elementry School 2 Sukodono - Sidoarjo Regency on the variables of communication, disposition and bureaucratic structure, has optimally supported policy implementation, but in the resource variable there are still limited budgets and infrastructure, so that the achievement of policy implementation is still limited. not optimal.Factors supporting this implementation include: a) good communication and coordination with the Ministry of Research, Technology and Higher Education/District Education Office, teachers, students and parents, b) adequate teacher human resources, BOS (School Operational Assistance) budget, c) ) the existence of school infrastructure, d) the seriousness of the principal, teachers, students and parents of students, e) the existence of a bureaucratic structure and channels of command in schools that can be used as channels of command to implement policies, f) there is a clear division of labor clear. While the inhibiting factors are a) the budget only relies on BOS (School Operational Assistance) funds, b) the lack of financial support from parents of students in P5 learning activities because the majority are from lower-income families, c) limited school infrastructure facilities, d) limited references to learning curriculum Independent, e) learning on. Grade 1 students practice making processed food and drinks using a stove, so they still need the assistance of parents and teachers.The researcher made a recommendation that Kloposepuluh State Elementry School 2 Sukodono - Sidoarjo Regency should propose an increase in the budget to support P5 learning and improve school infrastructure, seek potential funding to improve school infrastructure through the CSR (Corporate Social Responsibility) program from companies in the Sukodono area – Sidoarjo, increasing references to the Merdeka curriculum learning methods from various social media and comparative studies and practical learning that requires the use of a stove should be given to students in grades 4 and above. Keywords : Policy implementation, Independent Curriculum, Kloposepuluh State Elementry School 2 Sidoarjo